The intervention effect of Aitongxiao prescription on primary liver cancer rats was evaluated based on high-throughput miRNA sequencing and bioinformatics analysis - Xu, Lijing; Cheng, Jinlai; Li, Zhuoxian; Wen, Xiaoyu; Sun, Yuhao; Xia, Meng; Leng, Jing (Frontiers in Oncology, 2023)
Liver cancer is a common malignant tumor known for its difficult treatment and poor prognosis. As a traditional Chinese medicine prescription, Aitongxiao prescription (ATXP) has been used in clinical treatment of primary liver cancer (PLC) for more than ten years, and its therapeutic effect is obvious and has been verified over time. However, the mechanism of ATXP in treating PLC has not been fully elucidated. This study aimed to detect the liver-protective effect of ATXP on a PLC rat model and explore its potential mechanism from the perspective of plasma extracellular vesicle miRNAs. Fifty SPF male SD rats were randomly selected, with six rats as the control group, and the remaining rats were injected with DEN to establish a primary liver cancer model. The model rats were randomly divided into the model group and the ATXP group. After 4 weeks of intervention, the liver-protective effect of ATXP was evaluated using plasma biochemical indicators and histopathological methods. Plasma extracellular vesicles were isolated and extracted, and identified by transmission electron microscopy, nanoparticle tracking analysis, and western blot. Significant differentially expressed miRNAs in extracellular vesicles were screened by Illumina sequencing to explore the therapeutic targets of ATXP and conduct functional analysis. The results showed that ATXP significantly reduced plasma liver function in PLC rats and alleviated liver pathological damage. In addition, plasma extracellular vesicles were isolated and identified. According to the results of GO and KEGG analysis, they were related to multiple biological processes and covered multiple signaling pathways (PI3K-Akt and MAPK signaling pathways, etc.). The interaction between miR-199a-3p and MAP3K4 was determined by bioinformatics methods and dual-luciferase reporter gene detection, confirming that MAP3K4 is the target gene of miR-199a-3p. In conclusion, ATXP protects the liver from DEN-induced PLC, which may be related to the regulation of plasma extracellular vesicle miR-199a-3p. This study further reveals the mechanism of ATXP in treating liver cancer and provides a theoretical basis for subsequent research.